Genetic Detection of Neospora caninum in the Blood of Dairy Cattle from Boyacá, Colombia - Correa-Castro, Tania-Alejandra; Gómez-Palacio, Andrés-Mauricio; Pulido-Medellín, Martin-Orlando (Revista Científica, 2021)
Neospora caninum is a parasite of the phylum Apicomplexa that causes significant economic losses for cattle husbandry worldwide. Despite its relevance, information regarding infection prevalence in endemic areas of Colombia is scarce. Previous studies have reported a high seroprevalence in dairy cattle from Boyacá, which suggests a significant risk factor for active transmission of neosporosis. However, there is no available data concerning the infection stage or the presence of said parasite in the peripheral blood of dairy cattle. In this study, genetic detection of N. caninum was carried out using a nested PCR with an Nc-5 marker on peripheral blood samples from dairy cows in the municipalities of Paipa, Toca, and Tuta. Four positive samples were sequenced through the Sanger method, which were then edited, aligned, and compared to sequences available in the GenBank database. The parasite’s DNA was detected in 23 out of 170 analyzed blood samples. A qualitative detection limit was estimated ( 64 parasites per volume of blood sampled). This is the first report of DNA detection of N. caninum through PCR in blood from Colombian dairy cattle. Thereupon, further studies about N. caninum molecular detection and population genetics in cattle peripheral blood could be very useful for the early diagnosis of neosporosis and creating more effective epidemiological surveillance strategies.